YET ONE PLAGUE: A STUDY ON THE NARRATIVE FUNCTION AND LITERARY PLACE OF EXODUS 11:1-3 - Leal, Jônatas de Mattos (Práxis Teológica, 2016)
The present study has the objective of exploring the nature of the narrative of Exod 11, particularly, the literary and narrative function of verses 1-3, which abruptly interrupt the dialogue between Moses and Pharaoh in 10:24-29 and 11:4-8. While a plethora of suggestions have been made by the commentators of the text, no serious and more detailed analysis of the narrative elements of the passage has been carried out. That is why a closer look at these components in light of the strategies of the Hebrew narrative is proposed here. In fact, the knowledge and awareness of these strategies can help the modern reader of the Bible not only to understand the text but also to appreciate it even more.